A qualitative exploration of reunification post alienation from the perspective of adult alienated children and targeted parents - Matthewson, Mandy Louise; Bowring, Jessica; Hickey, Jacinta; Ward, Sophie; Diercke, Peta; Van Niekerk, Leesa (Frontiers in Psychology, 2023)
Introduction The aim of this study was to explore the experiences of voluntary reunification from the perspectives of adult alienated children and targeted parents Methods Nine adult alienated children and 12 targeted parents participated in semi-structured interviews which were transcribed verbatim and analyzed thematically Results Six themes emerged in the data from the adult alienated children including catalysts for reunification, factors influencing reunification, adult alienated child relationships, the role of communication in reunification, adult alienated child understandings of alienation post reunification, and the role of therapy in reunification. Three themes emerged from the targeted parents including what is reunification, factors impacting reunification, and life after reunification. Discussion Findings from the present study offer novel insights into the experience of voluntary reunification from the perspectives of both adult alienated children and targeted parents. They illustrate that voluntary reunification is a process that takes time. This process can span decades and can include periods of connection and rejection.